The 1st International Electronic Conference on Food Science and Functional Foods 2020
DOI: 10.3390/foods_2020-07649
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Pig Carcasses with Organic Acids

Abstract: This study aims to evaluate the efficiency of two organic acids as decontaminants in pig carcasses. A mix of Salmonella Typhimurium and Salmonella Derby bacterial suspensions were inoculated in rind samples of about 25 cm2 at two concentrations, 1.42 × 105 CFU/cm2 (Suspension A) and 4.92 × 106 CFU/cm2 (Suspension B). Samples were decontaminated by spraying with one of two organic acids at each of two concentrations: 2% or 5% of lactic acid or citric acid. Five different times were analyzed, 30 min, 6, 12, 24, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…From a systematic review, it was observed that in most studies on fresh meat treatment, the concentrations of OA were between 1-3% and are acceptable in the food industry [6]. Given the general contribution of AA and LA concentration change in the food industry [37,38].As a result of the contribution of AA and LA concentration change [40,41], a concentration of 5% as used in this study was expected to provide better results. While some traces of microbial reduction were observed around the gunshot pellet-and rifle bullet-inflicted wound areas, neither the water, 5% LA or 5% AA treatments proved to cause a meaningful reduction in the targeted microorganisms around the bullet wounds from the two killing methods.…”
Section: Effect Of Treatment Methods On Microbiological Countsmentioning
confidence: 92%
“…From a systematic review, it was observed that in most studies on fresh meat treatment, the concentrations of OA were between 1-3% and are acceptable in the food industry [6]. Given the general contribution of AA and LA concentration change in the food industry [37,38].As a result of the contribution of AA and LA concentration change [40,41], a concentration of 5% as used in this study was expected to provide better results. While some traces of microbial reduction were observed around the gunshot pellet-and rifle bullet-inflicted wound areas, neither the water, 5% LA or 5% AA treatments proved to cause a meaningful reduction in the targeted microorganisms around the bullet wounds from the two killing methods.…”
Section: Effect Of Treatment Methods On Microbiological Countsmentioning
confidence: 92%